Chest circumference and structural and short-term changes: a study of the Italian military call-up registers from 1881 to 1909. (2nd January 2023) - Fornasin, Alessio; Breschi, Marco; Manfredini, Matteo
ABSTRACT: The aim of this study is to demonstrate the utility of chest circumference measurements as a proxy for the socioeconomic characteristics of past populations. Our analysis is based on over 80, 000 military medical examinations relating to Friuli (north-eastern Italy), recorded from 1881 to 1909. Chest circumference can be used to describe changes in standard of living, but also seasonal variations in food intakes and physical activities. The findings show the way in which these measurements are highly sensitive not only to long-term economic changes but, above all, to short-term variations in some economic and social elements, like corn prices and occupations.